Effects of Structural Modification on the Thermostability of F1 Protease from Bacillus Stearothermophilus F1 - Ibrahim, Noor Azlina (2008)
A thermophilic Bacillus stearothermophilus F1 was found to produce an extremely thermostable serine protease. The F1 protease sequence was modeled onto the crystal structure of thermitase with 61% sequence identity. The F1 protease contains a catalytic triad comprising of Asp39, His72 and Ser226. The predicted structure of F1 protease comprised 10 α-helices and 10 β-sheets arranged in a single domain. Comparison of the predicted 3D structure of F1 protease with the crystal structure of serine proteases from mesophilic bacteria and archaea, led to the identification of features related to protein stabilization. Higher themostability was found to be correlated with an increased number of residues involved in ion pairs or networks of ion pair. In order to investigate F1 protease stability, two mutated (W200R and D58S) F1 protease were designed. The analysis of molecular dynamics simulations of W200R mutant revealed that an additional three new ion pairs between Arg200 and Asp202, however there was no ion pair interaction at position Ser58. To confirm the role of ion pair, site-directed mutagenesis was carried out. Both mutated F1 proteases were designed, cloned into pGEX-4T1 and expressed in E. coli BL21 (DE3) pLysS. The optimum expression level for the wild type F1 protease, W200R and D58S mutants were 94 U/mL, 112 U/mL and 68 U/mL, respectively. The wild type F1 protease, W200R mutant and D58S mutant were purified by affinity chromatography and heat-treatment. A single band was visible at SDS-PAGE at approximately 33.5 kDa. The purified wild type, W200R mutant and D58S mutant showed 95%, 115% and 64% recovery with purification fold of 21.7, 33.8, and 17.2, respectively. In the presence of 2 mM CaCl2, the wild type had half-lives of 60 min and 7 min at 85 ºC and 90 ºC. Meanwhile, the W200R mutant had half-lives of 75 min and 12 min at 85 °C and 90 ºC, which was more stable than wild type. The stability of W200R mutant was 1.25 times higher than that of the F1 protease. The enhanced thermostability can be correlated to the increase in the number of residues involving ion pairs and ion pairs networks. In contrast, the D58S mutant showed half-life of 45 min at 85 ºC but there was no enzymatic activity at 90 ºC. Thus, the D58S mutant was less thermostable than that wild type which could be due to the removal of ion pairs on this mutated F1 protease (computational work). Far-UV CD at 221 nm was used to detect the denatured proteins. As the temperature was increased from 50 °C to 90 °C, the change in ellipticity at 221 nm revealed a sigmoidal monophasic transition curve of mutant’s proteins which indicated unfolding of a protein.The melting point at pH 8.0 of the wild type F1 protease, W200R mutant and D58S mutant were 70 °C, 72 °C and 63 °C, respectively. Far-UV CD measurements studies indicated the overall features of the secondary structure of protein. The wild type contains 25.5% of α-helix, 17.7% of β-sheet, 22.5% of turn and 34.0% of random coil. There was some loss of β-sheet in W200R but a 3.8% and 1.7% increase in an α-helix and a random coil, respectively, indicated that Arg200 stabilized the α-helix content. The β-sheet was reduced to less than 4% and random coil rose up to more than 8%. A small decrease in the α-helix was observed in D58S mutant. This could be due to the substitution of Asp58 to Ser causing disruption of four ion pairs between Asp58 and Arg103, located at β-sheet. The results obtained confirmed the important role of intermolecular ion pairs in the stability of the whole structure of F1 protease. These results also showed that simulation procedures and molecular biology techniques can be used together to direct protein engineering and/ or site-directed mutagenesis.